Growth performance of stenotrophomonas maltophilia (SB16) in different culture media - Hashim, Noor Hidayah; Othman, Radziah; Ismail, Mohd Razi (Bangladesh Botanical Society, 2017)
An in vitro experiment was conducted to test the growth of Stenotrophomonas maltophilia (Sb16) in different media in laboratory. The treatments for different media were made by adding molasses (2.5, 5.0, 7.5, 10.0, 12.5, 15.0, 17.5 and 20.0 g w/v) as carbon sources compared to commonly used Nutrient Broth and Tryptic Soy Broth. Dry cell mass of S. maltophilia (Sb16), total reducing sugar and total N in culture media were determined. The highest growth of S. maltophilia (14.84 mg/ml) was observed at sugarcane molasses concentration 20% w/v after 24 hrs of incubation. Total reducing sugar increased with increasing molass concentration. High total N (505 mg/l) was ploduced in 7.5% w/v molasses concentration.